Effect of Diet on Type 2 Diabetes Mellitus: A Review - Sami, Waqas; Ansari, Tahir; Butt, Nadeem Shafique; Mohd Rashid, Ab Hamid (Qassim University, 2017)
Globally, type 2 diabetes mellitus (T2DM) is considered as one of the most common diseases. The etiology of T2DM is complex and is associated with irreversible risk factors such as age, genetic, race, and ethnicity and reversible factors such as diet, physical activity and smoking. The objectives of this review are to examine various studies to explore relationship of T2DM with different dietary habits/patterns and practices and its complications. Dietary habits and sedentary lifestyle are the major factors for rapidly rising incidence of DM among developing countries. In type 2 diabetics, recently, elevated HbA1c level has also been considered as one of the leading risk factors for developing microvascular and macrovascular complications. Improvement in the elevated HbA1c level can be achieved through diet management; thus, the patients could be prevented from developing the diabetes complications. Awareness about diabetes complications and consequent improvement in dietary knowledge, attitude, and practices lead to better control of the disease. The stakeholders (health-care providers, health facilities, agencies involved in diabetes care, etc.) should encourage patients to understand the importance of diet which may help in disease management, appropriate self-care and better quality of life.